CARE OF TULIP VARIETIES OF THE NETHERLANDS IN THE CLIMATIC CONDITIONS OF THE NAMANGAN REGION (American Journal of Interdisciplinary Research and Development, 2022)
This article research works on the growth and development of varieties introduced from the Netherlands in the climatic conditions of the Namangan region of the Republic of Uzbekistan and their originality was carried out. The experimental material, IE onions, consisted of 2 300 000 grains of introduced varieties from the Netherlands. Before planting, the technology of freezing was applied to the Tulip onions in 4–50 S harorat for 16 weeks. The main purpose of the study was to determine the varieties of onions resistant to all climatic conditions and diseases, as well as to compare local and introduced varieties, to determine the most optimal options.